Growth performance of pigs fed diets containing distillers dried tapioca pulp (DDCP), a by-product from ethanol manufacturing - Narumon, W.; Wittawat, W. (International Journal of Agricultural Technology, 2021)
The distillers dried tapioca pulp (DDCP) is a by-product, resulting from manufacture of ethanol that is an effective alternative feed source for pig diets. This study was investigated the effects of DDCP in dietary production performance during two growth phases of pigs; growing pigs (initial body weight being 27.59±2.36 kilogram) and fattening pigs (65.72±2.31 kilogram body weight). Results found that DDCP showed positive effects on production performance in both growing and fattening pigs. Inclusion of DDCP in diets at 5-15% for growing pigs had greater (p<0.05) body weight gain (BWG) and average daily gain (ADG) than those in control, with no significant differences among DDCP treated diet populations observed. However, only DDCP in diets at 10 to 15% had higher feed intake (FI) and average daily feed intake (ADFI). Results also found that inclusion of DDCP in diets at 20% for fattening pigs had highest final weight (FW), BWG and ADG (p<0.05); but lowest feed conversion ratio (FCR) and feed cost gain (FCG). In conclusion, these results indicated that DDCP can be incorporated in growing pig and fattening pig diets, up to 15% and 20%, respectively. However, DDCP at 5% and 20%, suggested to incorporate in growing pig and fattening pig diets due to, the best growth performances were observed with these diets